AlPO4-C composite coating for high emissivity and oxidation protection applications. (1st June 2013) - Roy, S; Maharana, R; Gokul Laxmi, S; Sakthivel, Y; Roy, M; Bhanu Prasad, V V; Das, D K
<x xml:space="preserve">Abstract</x> AlPO4-C coating deposited by sol-gel technique on Ni base superalloy substrate Nimonic-75 has been examined for high emissivity applications. The coating showed a spectral (2-25 μm wavelength) emissivity in the range of 0·8-0·91, and the emissivity increased with coating thickness. The coating exhibited a reasonably good adhesion with the substrate, as determined from nanoscratch test. The above coating also had a good oxidation resistance in air at 800 and 900°C under cyclic heating and cooling conditions.